Acute Cognitive Effects of the Dual Orexin Receptor Antagonist Lemborexant Compared With Suvorexant and Zolpidem in Recreational Sedative Users. Issue 4 (24th July 2022) - Landry, Ishani; Hall, Nancy; Alur, Jagadeesh; Filippov, Gleb; Reyderman, Larisa; Setnik, Beatrice; Henningfield, Jack; Moline, Margaret
Abstract: Purpose/Background: As part of a human abuse potential (HAP) study of lemborexant (LEM), the effects of therapeutic (LEM 10 mg), and supratherapeutic doses of LEM 20 mg and LEM 30 mg on cognition and psychomotor performance were compared with placebo (PBO) and supratherapeutic doses of zolpidem (ZOL) 30 mg and suvorexant (SUV) 40 mg. Subjects (n = 32) were healthy, nondependent, recreational sedative users able to discriminate the effects of both SUV and ZOL from PBO on subjective drug measures. Methods/Procedures: The human abuse potential study was a single-dose, randomized, double-blind, PBO-controlled, 6-way crossover study. Eligible subjects admitted to the treatment phase completed the choice reaction test (CRT) and divided attention test. The CRT included measurements of recognition reaction time (RRT) and motor reaction time. Findings/Results: Recognition reaction time and mean maximum change from baseline (CFBmax ) scores were significantly increased (slower performance) versus PBO for all LEM doses (all P < 0.001), ZOL ( P < 0.001), and SUV ( P = 0.004), and LEM (all doses) was not statistically different from ZOL or SUV. Motor reaction time and mean CFBmax versus PBO were significantly increased for all LEM doses (all P < 0.001), and ZOL ( P < 0.001) and SUV ( P < 0.001). All LEM doses showed significantly decreased (better performance) mean CFBmax versus ZOL (all P < 0.001), but not SUV. Notably, all cognitive effects in the CRT and divided attention test were limited to the main treatment phase (up to 8 hours postdose). Implications/Conclusions: All active doses of LEM, ZOL, and SUV generally increased reaction time and reduced divided attention capabilities versus PBO. However, at therapeutic/supratherapeutic doses, LEM led to significantly less cognitive impairment than supratherapeutic doses of ZOL in some measures.